PEMBERDAYAAN KADER MELALUI PELATIHAN PIJAT OKSITOSIN UNTUK PENCEGAHAN MASTITIS - Nugrawati, Nelly (Stikes Yarsi Mataram, 2024)
Oxytocin massage has proven effective in reducing the risk of mastitis in breastfeeding mothers by helping the breasts to relax and improving milk flow, thereby reducing swelling and milk duct blockages. Education on proper breastfeeding techniques is crucial to prevent worsening conditions and increasing the risk of mastitis. This community service activity aims to provide education and oxytocin massage training to posyandu cadres in the Puskesmas Pancana Makassar area. The community service method involves direct guidance from trained facilitators to the cadres, which includes proper and safe massage techniques as well as understanding the benefits for breastfeeding mothers, while cadre participation is documented and analyzed to evaluate the impact of the training on increasing knowledge and skills in oxytocin massage techniques and mastitis prevention. The results of this activity show that oxytocin massage training effectively enhances the practical skills of posyandu cadres, with 80% of cadres achieving good skills after the training compared to only 10% before the training, thus contributing to the prevention of mastitis and improving the quality of health services at posyandu. Integrating oxytocin massage into posyandu cadre training programs is crucial in preventing mastitis, enhancing maternal mental health, and strengthening the emotional bond between mother and baby. Therefore, this training not only improves the practical knowledge of cadres but also has a significant positive impact on supporting family health and well-being at the community level.